Legacies of Racial Violence: Clarifying and Addressing the Presence of the Past. (March 2021) - Cunningham, David; Lee, Hedwig; Ward, Geoff
Scholars increasingly agree that histories of racial violence relate to contemporary patterns of conflict and inequality, and growing interest exists among civic leaders in reckoning with these legacies today. This volume examines the contributions and limitations of scientific research on legacies of racial violence and suggests implications for policy, practice, and other forms of intervention aimed at redress.